PENGARUH INTENSITAS MENGIKUTI KEGIATAN KEAGAMAANTERHADAP PERILAKU SOSIAL ISLAMI PESERTA DIDIK KELAS XI SMA NEGERI 6 JENEPONTO - Muh.Yusuf Hidayat; Abd.Syukur Abu Bakar; Risna Mosiba (Inspiratif Pendidikan, 2023)
This research aims to: 1) Describe the intensity of participating in religious activities of class XI students at SMA Negeri 6 Jeneponto; 2) Describe the Islamic social behavior of class XI students at SMA Negeri 6 Jeneponto; 3) Testing the influence of the intensity of participating in religious activities on the Islamic social behavior of class XI students at SMA Negeri 6 Jeneponto. This type of research is quantitative research using an ex post facto method with a simple linear regression research design. This research was conducted at SMA Negeri 6 Jeneponto. The population in this study was class XI students at SMA Negeri 6 Jeneponto, totaling 360 people. Meanwhile, the sample in this study was 50 people using a simple random sampling method. Data collection in this research used a questionnaire instrument which was analyzed using descriptive and inferential statistics. Based on the results of the descriptive analysis, it can be concluded that the intensity of participating in religious activities for class XI students at SMA Negeri 6 Jeneponto is in the medium category with a percentage of 70%. Meanwhile, the Islamic social behavior of class XI students at SMA Negeri 6 Jeneponto is also in the medium category with a percentage result of 66%. From the results of the analysis, tcount = 2.98, while the implication value ttable = 1.677 for a significance level of 5%. Because tcount is greater than ttable, it can be concluded that H0 is rejected and HI is accepted. This means that there is an influence of the intensity of participating in religious activities on the Islamic social behavior of class XI students at SMA Negeri 6 Jeneponto. The implication of this research is that school principals should implement more familiarization with religious activities at school. Because an institution managed by a leader who has a strong Islamic commitment and broad insight will run orderly and dynamically. Islamic religious education teachers should use several methods in delivering material which must be supported by example or the habit of good attitudes. Because without habituation, the implementation of religious activities will be less than optimal. Students should get used to following and deepening religious qualities and carrying out activities with positive values to avoid negative things. For future researchers, this research can be used as reference material in conducting research on religious activities and Islamic social behavior.